Archive, photography and the language of administration - Birkin, Jane (Amsterdam University Press, 2021)
This alternative study of archive and photography sits firmly against the backdrop of the traditional archive. Although many types of image assemblages feature-public and private, formal and informal, physical and digital-they are all considered in relation to the highly regulated systems that operate within the institutional milieu. Cataloguing is presented as a radical form of knowledge production, and the catalogue as a critical tool for mapping image time. The unfamiliar and overlooked language of image description is considered as having a life, a worth and an aesthetic value of its own. Functioning at the intersection of text and image, this book combines media culture and techniques of the archive, as well as contemporary discourse on art and conceptual writing. There is a media-archaeological debate throughout as to how physical archive systems and material technologies connect with different archival models, including social media spaces and other image networks
Keywords: Art and Material Culture; Film, Media and Communication; Interdisciplinary Studies; Media Art and Visual Cultures; Media Studies; New Media and Technology; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / Archives & Special Libraries; Archival materials; Cataloging of archival materials; Cataloging of pictures; Photography -- Archive applications; Fotografie; Bestandserschließung; Archivbestand